Urgensi Model Komunikasi Dua Arah pada Proses Pendidikan - Ibnu Fiqhan Muslim; Fahmi Salsabila; Priyono Priyono (INTELEKTIUM, 2022)
In dealing with students who have different characters, of course an educator must be able to adapt to each of their students. The process of communication that is two-way, namely between educators and students can be well established. In the educational process, communication is also an important instrument that must be realized effectively so that the purpose of education is to provide understanding to students. The material presented by the teacher will be conveyed and received well by the students. Therefore, two-way communication is important for the achievement of meaningful learning. This research uses the scientific method through literature review or literature study using theories related to the discussion in the research. Two-way communication occurs when there is a response/feedback from the other person when communicating. Two-way communication is communication that is complete because the information that occurs in this type of communication flows between the sender and the recipient of the information. Communication between educators and students must be realized properly. There are many effective communication models that can be used by educators in conveying information or messages to their students and one of them is a two-way communication model..